High Resolution UHPLC-MS Metabolomics and Sedative-Anxiolytic Effects of Latua pubiflora: A Mystic Plant used by Mapuche Amerindians - Sánchez-Montoya, Eliana L.; Reyes, Marco A.; Pardo, Joel; Nuñez-Alarcón, Juana; Ortiz, José G.; Jorge, Juan C.; Bórquez, Jorge; Mocan, Andrei; Simirgiotis, Mario J. (Frontiers in Pharmacology, 2017)
Latua pubiflora (Griseb) Phil. is a native shrub of the Solanaceae family which grows freely in southern Chile and is employed among Mapuche aboriginals to induce sedative effects and hallucinations in religious or medicine rituals since prehispanic times. In this work, the pentobarbital-induced sleeping test and the elevated plus maze test were employed to test the behavioural effects of extracts of this plant in mice. The psychopharmacological evaluation of L. pubiflora extracts in mice determined that both alkaloid-enriched as well as the non-alkaloid extracts produced an increase of sleeping time and alteration of motor activity in mice at 150 mg/Kg. The alkaloid extract exhibited anxiolytic effects in the elevated plus maze test, which was counteracted by flumazenil. In addition, the alkaloid extract from L. pubiflora decreased [H3]-flunitrazepam binding on rat cortical membranes. In this study we have identified 18 tropane alkaloids (peaks 1-4, 8-13, 15-18, 21, 23, 24 and 28), 8 phenolic acids and related compounds (peaks 5-7, 14, 19, 20, 22 and 29) and 7 flavonoids (peaks 25-27 and 30-33) in extracts of L. pubiflora by UHPLC-PDA-MS which are responsible for the biological activity. This study assessed for the first time the sedative-anxiolytic effects of L. pubiflora in rats besides the high resolution metabolomics analysis including the finding of pharmacologically important tropane alkaloids and glycosylated flavonoids.